2005
DOI: 10.1186/1471-2350-6-41
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Flavin containing monooxygenase 3 (FMO3) gene do not predispose to essential hypertension in Caucasians

Abstract: BackgroundThe recessive disorder trimethylaminuria is caused by defects in the FMO3 gene, and may be associated with hypertension. We investigated whether common polymorphisms of the FMO3 gene confer an increased risk for elevated blood pressure and/or essential hypertension.MethodsFMO3 genotypes (E158K, V257M, E308G) were determined in 387 healthy subjects with ambulatory systolic and diastolic blood pressure measurements, and in a cardiovascular disease population of 1649 individuals, 691(41.9%) of whom had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…For example, certain FMO3 polymorphisms are not associated with common diseases such as colorectal cancer and hypertension [68,69]. This is one gray area illustrative of the amount of additional research needed to establish the significance of FMO3 polymorphisms in human diseases and their management.…”
Section: Resultsmentioning
confidence: 99%
“…For example, certain FMO3 polymorphisms are not associated with common diseases such as colorectal cancer and hypertension [68,69]. This is one gray area illustrative of the amount of additional research needed to establish the significance of FMO3 polymorphisms in human diseases and their management.…”
Section: Resultsmentioning
confidence: 99%
“…This raises the interesting prospect that drugs selectively targeting FMO3 might have some utility in diabetes and hyperlipidaemia, particularly when elevated TMAO levels suggest that hepatic FMO3 expression is high. However, since FMO3 plays a systemic role in catecholamine metabolism, suppressing its function might not prove to be innocuous; genetic absence of FMO3 activity has been associated with hypertension 147. In any case, when hepatic insulin resistance is present, correcting this should lessen hepatic FMO3 expression.…”
Section: Fmo3 Might Also Mediate Risk Associated With Elevated Tmaomentioning
confidence: 99%
“…The proposed mechanism was that FMO3 could metabolize tyramine, an endogenous pressor molecule, thereby reducing its pressor effects and lowering blood pressure (43). A follow-up study found that none of three examined FMO3 polymorphisms predispose to hypertension in a sample of several hundred Caucasian patients, but also noted that severe, highly penetrant loss-of-function mutations could "unmask pressor effects of variation in other drug metabolizing enzymes previously buffered by FMO3" (51). At least two more recent studies are consistent with TMAO production having a reactive, protective function in response to CVD pathology (52,53), with one of these studies asserting that TMAO is, in fact, protective against CVD risk (53).…”
Section: Atherosclerosis and Cardiovascular Disease (Cvd)mentioning
confidence: 99%